2010
DOI: 10.1364/oe.18.003967
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic ophthalmoscopy for in vivo retinal imaging

Abstract: We have developed a non-invasive photoacoustic ophthalmoscopy (PAOM) for in vivo retinal imaging. PAOM detects the photoacoustic signal induced by pulsed laser light shined onto the retina. By using a stationary ultrasonic transducer in contact with the eyelids and scanning only the laser light across the retina, PAOM provides volumetric imaging of the retinal micro-vasculature and retinal pigment epithelium at a high speed. For B-scan frames containing 256 A-lines, the current PAOM has a frame rate of 93 Hz, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
258
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(259 citation statements)
references
References 23 publications
0
258
0
1
Order By: Relevance
“…This article demonstrated high-resolution PAI of ex vivo eyes. Zhang et al, [22] showed a system simultaneously acquired photoacoustic ophthalmoscopy (PAOM) and OCT B-scan images of eyes. They demonstrate contrast mechanism of PAOM is that the stronger the optical absorption, the stronger the generated ultrasonic signals.…”
Section: Applications Of Paimentioning
confidence: 99%
“…This article demonstrated high-resolution PAI of ex vivo eyes. Zhang et al, [22] showed a system simultaneously acquired photoacoustic ophthalmoscopy (PAOM) and OCT B-scan images of eyes. They demonstrate contrast mechanism of PAOM is that the stronger the optical absorption, the stronger the generated ultrasonic signals.…”
Section: Applications Of Paimentioning
confidence: 99%
“…Moreover, a photoacoustic imaging system, such as a transducer and a data acquisition unit, is similar to a conventional ophthalmic ultrasound imaging system and effectively combined with it so that it is feasible to offer mechanical and morphological information in addition to functional and cellular data [10,11]. However, recent studies related to photoacoustic ophthalmic imaging have been mostly based on a single element detector and focused on assessment of microscopic structure, which is confined to limited field of view and far from fully utilizing potentials and advantages of photoacoustic imaging techniques [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it plays an important role in the maintenance of retinal homeostasis and is implicated in a majority of retinal diseases due to the failure of RPE functions [3][4][5] . An imaging method to examine RPE cells for retinal pathological analysis is needed.Photoacoustic microscopy (PAM) is a noninvasive and label-free three-dimensional imaging modality based on the optical absorption property of biological tissues [6][7][8][9] , which has proved its capacity for in vivo imaging of blood vessels and RPE in fundus [10][11][12][13] . To achieve the cellular or subcellular imaging level, PAM systems have been developed to achieve micrometer or submicrometer resolution and used for imaging red blood cells and pigment cells [7,14,15] .…”
mentioning
confidence: 99%